Negotiating the Challenges of Coerced Treatment: An Exploratory Study of Community-Based Service Providers in Queensland, Australia. (December 2013) - Thomas, Natalie K.; Bull, Melissa
The use of legal pressure to convince drug users to access treatment has become a popular drug-policy strategy in Australian and international jurisdictions. Providing drug treatment in this context necessitates partnerships between criminal justice agencies and drug treatment and support agencies, including community-based agencies. Drawing on data from qualitative interviews, this article explores the issues that coerced treatment presents for community-based service providers. We employ the analytics associated with Foucault's notion of governmentality to "make sense" of our research findings. We argue that these service providers negotiate the challenges of working in a criminal justice context by treating their clients as "informed choice-makers, " and by employing more liberal techniques of governance that rely on the possibility of freedom as well as the threat of constraint.